Fundamental of Entrepreneurship ENT300 : Santai Cybercafe / Nurul Hidayah Atikah Abdullah ... [et al.] - Abdullah, Nurul Hidayah Atikah; Md Rosidi, Rosmawaddah; Suliman, Nursafarina; Esmani, Nurrini (2014)
Santai Cybercafe is a business that serves internet and computer service to the customer which located at Kuching, Sarawak. Santai Cybercafe offer fast Internet surfing service to people that may not have Internet access in their home. Therefore, Santai Cybercafe wants to provide it. All range of age like teenager, adult and children are welcome to come to Santai Cybercafe. We believe that Santai Cybercafe can achieve high profit because Santai Cybercafe serve customer with a good service. The workers will help customer if there is any problem occurred while customer are in Santai Cybercafe. Moreover, Santai Cybercafe also provides additional service like selling drink and junk foods. Santai Cybercafe also has printing and photocopy service to those who need to print or photocopy anything. Therefore, Santai Cybercafe is really a convenient cybercafe that offer three services at once.